Biofilters as Alternative Method for Ammonia Removal in Water Treatment Plant - Abu Hasan, Hassimi; Hafizuddin Muhamad, Mohd; Nadia Mohd Sabri, Nurul; Rozaimah Sheikh Abdullah, Siti (International Journal of Engineering and Technology, 2019)
High level of ammonia concentration in raw water have led to the temporary shutdown of water treatment plant at certain areas of Malaysia especially in Selangor state. The contamination occurred as a result of the impact of industrial activities, agricultural activities and disposal of rubbish into the river. This study was carried out to determine the performance of slow sand biofilters (BioSSF) as an alternative method for the ammonia removal in drinking water treatment plant. Two factors i.e., empty bed contact time (EBCT) (5 to 15 minutes) and ammonia concentration (3 to 5 mg/L) were investigated. The results showed the best ammonia removal percentage was at 15 minutes EBCT with removal percentage of 98.3%. Increasing the ammonia concentration in raw water reduced the BioSSF performance, but the ammonia removal was still below the regulated limits (< 1.5 mg/L). In addition, the BioSSF also have a capability to reduce the turbitidy, chemical oxygen demand, colour and suspended solid. Thus, it proved the BioSSF can be an alternative method for the current conventional water treatment specially to remove the ammonia. Â Â